2007
DOI: 10.1158/0008-5472.can-06-1945
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated Recombinant Human Arginase (rhArg-peg5,000mw) Inhibits the In vitro and In vivo Proliferation of Human Hepatocellular Carcinoma through Arginine Depletion

Abstract: Hepatocellular carcinoma (HCC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
278
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(306 citation statements)
references
References 31 publications
22
278
0
6
Order By: Relevance
“…Interestingly, O-ASCs secrete arginine under arginine-deprivation conditions and this secreted arginine was uptaken by cancer cells, thereby increases NO synthesis and cancer cells' growth rate. Arginine depletion is currently used as a therapy for melanoma and hepatocellular carcinoma (31,32). We showed that when O-ASC-secreted arginine is depleted (using L-arginase) or when O-ASC-secreted factors induced increased NO synthesis in cancer cells is inhibited (using L-NAME), there is a decline in the growth rate of both ovarian cancer and endometrial cancer cells.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, O-ASCs secrete arginine under arginine-deprivation conditions and this secreted arginine was uptaken by cancer cells, thereby increases NO synthesis and cancer cells' growth rate. Arginine depletion is currently used as a therapy for melanoma and hepatocellular carcinoma (31,32). We showed that when O-ASC-secreted arginine is depleted (using L-arginase) or when O-ASC-secreted factors induced increased NO synthesis in cancer cells is inhibited (using L-NAME), there is a decline in the growth rate of both ovarian cancer and endometrial cancer cells.…”
Section: Discussionmentioning
confidence: 92%
“…However, recently Cheng et al have studied 5 HCC cell lines (HepG2, Hep3B, PLC/PRF/5, Huh7 and Sk-HEP-1) and reported that these cell lines express ASS and are not sensitive to ADI [30]. On the other hand, these cell lines lack OCT expression and are sensitive to arginase [30].…”
Section: Antitumor Activity Of Adi-peg20 In Hepatocellular Carcinomamentioning
confidence: 99%
“…These drawbacks may explain why the development of arginase as an antitumor agent has failed despite its activity seen in vitro [28,29]. Nevertheless, recently pegylated arginase has been shown to have activity in hepatocellular carcinoma both in vitro and in vivo due to lack of OCT expression in certain hepatocellular carcinoma cell lines [30]. On the other hand, arginine deiminase, a microbial enzyme from mycoplasma which catabolizes arginine to citrulline and ammonia, is more attractive due to the fact that tumor cells which lack ASS will not be able to synthesize intracellular arginine from citrulline while normal cells are able to regenerate arginine.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, rhArg demonstrates a promising novel agent for prostate cancer treatment (Cheng et al, 2007).…”
Section: Recombinant Human Arginase (Rharg)mentioning
confidence: 86%
“…Recombinant human arginase (rhArg) demonstrated significant cytotoxicity in hepatocellular carcinoma and melanoma, in vitro and in vivo (Cheng et al, 2007;Lam et al, 2009;Lam et al, 2010). In contrast to ADI-PEG20, the sensitivity to rhArg in hepatocellular carcinoma and melanoma is independent of ASS expression.…”
Section: Recombinant Human Arginase (Rharg)mentioning
confidence: 99%